2023
DOI: 10.2196/43885
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of the Supportive Parenting App on Infant Developmental Outcomes: Longitudinal Study

Abstract: Background Previous studies have investigated the various effects of parenting on infant developmental outcomes. In particular, parental stress and social support have been found to significantly affect the growth of the newborn. Although many parents today use mobile apps to obtain more support in parenting and perinatal care, few studies have examined how these apps could affect infant development. Objective This study aimed to examine the effectivene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Later into the postpartum period, the women were able to better choose appropriate and regular feeding patterns, recognise their baby’s needs, and soothe their crying or upset baby. Hence, postpartum stress associated with infant nurturing was reduced, and it only increased if the baby developed any health issues 55–57. Studies also found that maternal postpartum mental health may benefit from positive father engagement in infant care,58 59 and higher father engagement may mitigate maternal stress associated with infant sleep disturbances 60.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later into the postpartum period, the women were able to better choose appropriate and regular feeding patterns, recognise their baby’s needs, and soothe their crying or upset baby. Hence, postpartum stress associated with infant nurturing was reduced, and it only increased if the baby developed any health issues 55–57. Studies also found that maternal postpartum mental health may benefit from positive father engagement in infant care,58 59 and higher father engagement may mitigate maternal stress associated with infant sleep disturbances 60.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, postpartum stress associated with infant nurturing was reduced, and it only increased if the baby developed any health issues. [55][56][57] Studies also found that maternal postpartum mental health may benefit from positive father engagement in infant care, 58 59 and higher father engagement may mitigate maternal stress associated with infant sleep disturbances. 60 Most Chinese fathers do not observe gender role boundaries in child rearing and are reported to be actively involved in childcare activities, such as feeding and bathing.…”
Section: Discussionmentioning
confidence: 99%